DOIs for DICOM Raw Images: Enabling Science Reproducibility - Bourne, Philip E. (Radiology, 2015)
By being a front-runner, the imaging community has everything to gain, because original DICOM raw data exposure to the wider science audience is likely to speed standardized image acquisition as well as engender greater confidence in the clinical imaging literature.